Specificities of the science of educational rehabilitation in Central and Eastern Europe - Bouillet, Dejana (Special Education, 2017)
Scientific journals are amongst the most important sources of information regarding the status, content and other relevant characteristics of educational rehabilitation. A content analysis of scientific journals in an area illuminates its main trends and development. This work seeks to analyse basic trademarks of educational rehabilitation practice in countries from Central and Eastern Europe, specifically 15 post-socialist countries which have, during the 1990s, seen substantial political and social changes.  This research includes 4 scientific journals in which educational rehabilitation scientists have published most of the existing scientific work during the period from 2008 to 2016. These are: Croatian Review of Rehabilitation Research, Journal of Special Education and Rehabilitation, Research in Developmental Disabilities and Special Education. This research is based on an analysis of 273 published abstracts, by means of quantitative content analysis.The main hypothesis was that educational rehabilitation science in European post-socialist countries has recognisable content and method, with the primary purpose of developing scientifically verified interventions.  These contribute to the promotion of developmental, educational and social status for people with various difficulties. Such a hypothesis has been partially confirmed. It was established that there is recognisable content and method, but the predominance of scientifically verified interventions has not been established. The science of educational rehabilitation is primarily characterised by themes of specific abilities of a certain group of people with disabilities. This includes an analysis of the efficiency of various interventative methods being present in one third of the publications. In conclusion, the results of this research indicate the need for further improvement of scientific activities within the science of educational rehabilitation in Central and Eastern Europe, both in diversity of the scientific methodology and regarding a focus on the interventions themselves (including evaluation, but also the theoretical basis regarding their meaningfulness).
Keywords: content analysis; educational rehabilitation science; Central and Eastern Europe; scientific journals